Implementation of a labor market program with more frequent meetings in Sweden - Maria Cheung; Johan Egebark; Anders Forslund; Lisa Laun; Magnus Rödin; Johan Vikström (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2020)
In 2015, the Swedish Public Employment Service (PES), together with the Institute for Evaluation of Labour Market and Education Policy (IFAU), launched a large-scale randomized control trial to collect new evidence on direct and displacement effects of job search assistance (JSA). The JSA program introduced more frequent meetings between case workers and job seekers during the early phase of an unemployment spell, and involved three types of meetings: (1) individual face-to-face meetings, (2) individual distance meetings, and (3) group meetings. The purpose of this paper is to present details of the design of the experiment, as a background for the evaluation of the job search assistance program reported in a companion paper.
Keywords: C93; J68; 330; counseling; job search; randomized experiment